2015
DOI: 10.5206/cjsotl-rcacea.2015.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Surveying Assessment in Experiential Learning: A Single Campus Study

Abstract: The purpose of this study was to determine the methods of experiential assessment in use at a Canadian university and the extent to which they are used. Exploring experiential assessment will allow identification of commonly used methods and facilitate the development of best practices of assessment in the context of experiential learning (EL) at an institutional level. The origins of EL are found in the work of Dewey (1938), later modified by Kolb and Fry (1975). Experiential methods include: experiential edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This finding is similar to that of Struyven et al (2008b) who also found that students appreciated structure (in the form of the lecture). Such a result might also indicate the familiarity students have with the essay as it is a common assessment method in both traditional and in experiential learning environments (Yates et al, 2015). However, in the end, the essay was not preferred over the case study and the presentation possibly because the essay was a form of assessment that did not follow logically from the learning experience; similar to Struyven et al (2008a) who reported students did not prefer multiple choice following an activated learning experience.…”
Section: Comparison Of Preferences and Assessment Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…This finding is similar to that of Struyven et al (2008b) who also found that students appreciated structure (in the form of the lecture). Such a result might also indicate the familiarity students have with the essay as it is a common assessment method in both traditional and in experiential learning environments (Yates et al, 2015). However, in the end, the essay was not preferred over the case study and the presentation possibly because the essay was a form of assessment that did not follow logically from the learning experience; similar to Struyven et al (2008a) who reported students did not prefer multiple choice following an activated learning experience.…”
Section: Comparison Of Preferences and Assessment Resultsmentioning
confidence: 95%
“…Of these methods, the journal and the essay were individually completed assessments, whereas the case study and the presentation were group assessments. The essay was a form of traditional assessment, compared to the case study, journal, and presentation which were considered to be experiential (Yates et al, 2015). The specific questions asked by the assessment were designed by the researchers for the context of the learning experience.…”
Section: Experiential Assessment Pilot Methodologymentioning
confidence: 99%
See 3 more Smart Citations